2013
DOI: 10.1097/qad.0b013e32835c1333
|View full text |Cite
|
Sign up to set email alerts
|

Markers of microbial translocation and risk of AIDS-related lymphoma

Abstract: The association of sCD14 and LPS with NHL risk supports an etiologic role for gut microbial translocation in lymphomagenesis among HIV-infected individuals. Additional studies with larger sample sizes are needed to confirm these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 26 publications
2
42
0
3
Order By: Relevance
“…Our study found an association between B-cell TL2-expression/signaling and the etiology of AIDS-NHL. An association between the serum levels TLR4-ligand lipopolysaccharide (LPS) and the etiology of AIDS-NHL has been reported [25], suggesting that LPS stimulation contributes to B-cell hyperactivation, a critical driver of AIDS-NHL genesis. However, our previous data suggest TLR2 stimulation is a potent mediator of B-cell activation and HIV-infected subjects on ART exhibit higher serum levels of the TLR2-ligand lipoteichoic acid (LTA) [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Our study found an association between B-cell TL2-expression/signaling and the etiology of AIDS-NHL. An association between the serum levels TLR4-ligand lipopolysaccharide (LPS) and the etiology of AIDS-NHL has been reported [25], suggesting that LPS stimulation contributes to B-cell hyperactivation, a critical driver of AIDS-NHL genesis. However, our previous data suggest TLR2 stimulation is a potent mediator of B-cell activation and HIV-infected subjects on ART exhibit higher serum levels of the TLR2-ligand lipoteichoic acid (LTA) [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that anti-C burnetii antibody seroprevalence would be higher in individuals with AIDS-related NHL relative to the general HIV-positive population. To test this, we performed a nested case control study using stored serum and plasma samples from 2 previously published prospective cohort studies, the District of Columbia/New York Gay Men's Cohort (DCG) [9][10][11] and the AIDS Cancer Cohort Study (ACC). [10][11][12][13][14][15] Patients with incident (n 5 29) and prevalent (n 5 39) AIDS-NHL were matched by age, sex, and CD4 count to 67 HIV-positive controls (Table 1).…”
mentioning
confidence: 99%
“…[4][5][6] Collectively, our findings suggest that rates of infection with C burnetii are similar among HIV patients with and without NHL, indicating that C burnetii infection is not a risk factor for NHL in this setting. Yong Cheng, 9 Chunliang Li, 10 Allen Eng-Juh Yeoh, 5,6 Ching-Hon Pui, 11,12 Anders Jacobsen Skanderup, 4 and Jun J. Yang…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of AIDS, Marks et al [1] have reported significant associations between markers of microbial translocation and increased risk for non-Hodgkin's lymphoma (NHL) in HIV-infected individuals. The authors examined prediagnostic blood samples from NHL and non-NHL HIV-infected individuals for different markers of microbial translocation.…”
mentioning
confidence: 99%